Simultaneous extraction and fractionation of pufa from tropical tuna (thunnus tongol) head using pressure swing technique of supercritical CO2 (SC-CO2) - Sarker, Md. Zaidul Islam (2012)
Tuna fishes are known as one of the main commodity of fisheries which is generally marketed as canned food or as loins/steaks. Tuna head is about 25% of body weight and discarded as processing leftover during canning process. The objective of this study was to use this fish waste (head) as a source of fish oil especially PUFA. Simultaneous extraction and fractionation of PUFA from tuna head were conducted using pressure swing technique of SC-CO2. The dry and grinded sample was pressurised with pure CO2 and then soaked in the vessel for 1 hrs, and extracted continuously for 20 min at optimal conditions of 35 MPa, 65 oC, 3 ml min-1. The pressurization-soaking-extraction treatment was denoted as “pressure swing method” in this study. The total fish oil (13.11 g/100 g wt.) from head was extracted in 7 successive pressurization-soaking-extraction steps and the yield of each step was defined as fractional yield. Fatty acid constituents of each fractional yield were analyzed separately by gas chromatography. The short chain fatty acid constituents were found to be extracted mainly in the first 3 fractions and the next 4 fractions were predominant in MUFA and PUFA. Significant amount of DHA (26.83%) were extracted from fraction 4 followed by fraction 7. During the holding periods the liquid CO2 penetrated into the sample matrix and dissolved the readily soluble SFA portion of the oil which was eluted preferentially faster compared with either MUFA or PUFA. Therefore, multiple pressure swing steps could extract and fractionate the short chain fatty acid from relatively less soluble portions of long chain PUFA-rich sample matrix. However, PUFA-rich fraction extracted from tuna head may effectively serve as a source of EPA and DHA in food and pharmaceutical industries.